Design, Implementation and Performance Analysis of a Microcontroller based Wireless Electromyography Device - Aktan, Mehmet Emin; Goker, Imran; Akdogan, Erhan; Ozturk, Bedirhan (IEEE, 2017)
Elektromyography (EMG) signals are the electrical signals that are emerged by muscular contraction. In this study, a wireless EMG device was designed and implemented. The EMG signals are collected by surface electrodes, processed with filters and amplifiers and sent to the computer via wireless module. The EMG signals are obtained and amplified by an instrumentation and an inverting amplifier. Then, filtering is performed to remove noise. Two arduino microcontrollers and two nRF24L01 wireless communication modules are used as a receiver and a transmitter to perform wireless communication. The results were compared with the BIOPAC EMG100C and the difference of 5,3% was detected. The developed system will contribute scientific and economically considering the selling prices of the existing systems to our country.
Keywords: electromyography; wireless communication; Engineering